2021
DOI: 10.3390/ijms22020532
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the SARS-CoV-2–Host Protein–Protein Interactome by Affinity Purification Mass Spectrometry and Proximity-Dependent Biotin Labeling: A Rational and Straightforward Route to Discover Host-Directed Anti-SARS-CoV-2 Therapeutics

Abstract: Protein–protein interactions (PPIs) are the vital engine of cellular machinery. After virus entry in host cells the global organization of the viral life cycle is strongly regulated by the formation of virus-host protein interactions. With the advent of high-throughput -omics platforms, the mirage to obtain a “high resolution” view of virus–host interactions has come true. In fact, the rapidly expanding approaches of mass spectrometry (MS)-based proteomics in the study of PPIs provide efficient tools to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 116 publications
(283 reference statements)
0
50
0
Order By: Relevance
“…Amici et al [28] described indomethacin's antiviral activity against SARS-CoV in vitro in Vero E6 cells and in human epithelial lung cells. [29][30][31][32]. In humans, naproxen has been added to oseltamivir and clarithromycin for the treatment of influenza, which resulted in a significantly reduced 30-day mortality, intensive care unit stay, and hospitalization in general [33].…”
Section: Discussionmentioning
confidence: 99%
“…Amici et al [28] described indomethacin's antiviral activity against SARS-CoV in vitro in Vero E6 cells and in human epithelial lung cells. [29][30][31][32]. In humans, naproxen has been added to oseltamivir and clarithromycin for the treatment of influenza, which resulted in a significantly reduced 30-day mortality, intensive care unit stay, and hospitalization in general [33].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, results reported by Amici et al indicate that INM does not affect virus infectivity, binding or entry into host cells, but acts at an early stage of coronaviruses replication cycle, causing a global repression of viral protein synthesis via a ds-RNA-dependent protein kinase R (PKR)-mediated pathway [ 26 ]. On the other hand, a recently published proteomic/chemoinformatic study on the SARS-CoV-2 interactome with human host proteins suggested that the anti-SARS-CoV-2 activity of INM could be ascribed to its ability to inhibit human prostaglandin E synthase type 2 (PGES-2, encoded by PTGES2 ) [ 21 , 29 , 30 ]. In fact, INM has been previously reported as PGES-2 inhibitor in the low nanomolar range [ 25 , 31 ] and PGES-2 has been found to interact with the SARS-CoV-2 NSP7 protein [ 21 , 29 ], which, along with NSP8, is a non-structural viral protein composing the viral primase complex that is part of the viral RNA polymerase machinery.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, INM has been previously reported as PGES-2 inhibitor in the low nanomolar range [ 25 , 31 ] and PGES-2 has been found to interact with the SARS-CoV-2 NSP7 protein [ 21 , 29 ], which, along with NSP8, is a non-structural viral protein composing the viral primase complex that is part of the viral RNA polymerase machinery. Interestingly, PGES-2 resulted as a host proviral factor and the interaction between NSP7 and PGES-2 was found to be conserved across the three highly pathogenic CoVs SARS-CoV, SARS-CoV-2, and MERS-CoV [ 29 , 30 ], suggesting that PGES-2 may be a potential pan-CoV antiviral target, i.e., a target shared by all pathogenic CoVs that could be exploited for the development of universal anti-CoV strategies (from the Greek πᾶν, pan, meaning “involving all members” of a group).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of mass spectrometry in COVID-19 context focus on the search for augmented human inflammatory molecules to be used as biomarkers to assess the severity status of COVID-19 (see for example the work 4 of Messner and colleagues). Different studies report the use of proteomic approaches to characterise SARS-CoV-2 proteins [5][6][7] . Other studies highlight challenges in their use due to the need of enriching the protein fraction to be analysed for maximizing the technology sensitivity.…”
Section: Introductionmentioning
confidence: 99%